A new historicist analysis of gendered history in Mo Yan’s Soaring - Anwei Tu,; Halimah Mohamed Ali, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Mo Yan critically examines Chinese history and culture, focusing on the experiences of ordinary people within specific historical moments. His work provides a more personable and relatable perspective on history. Through the lens of new historicism, this paper will examine how literature and history intertwine in Mo Yan’s short story Soaring. By applying Louise Montrose’s concepts of historicity of texts and textuality of history, the paper will explore how historical narratives are not neutral but rather constructed and contested within literary texts. Additionally, by employing De Beauvoir’s concept of the Other, this paper investigates how Mo Yan’s female characters navigate the historical and patriarchal forces shaping their agency. Mo Yan’s portrayal of female characters in the story reflects the cultural tensions of 1980s, China. By integrating New Historicist and feminist perspectives, this study provides a deeper understanding of Mo Yan’s engagement with history and gender, contributing to broader discussions on the role of literature in reconstructing marginalised voices within historical discourse.